2003
DOI: 10.1038/sj.bjc.6601323
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of p53 status at the gene, chromosomal and protein levels in oesophageal adenocarcinoma

Abstract: p53 mutations and loss of heterozygosity have been commonly associated with oesophageal adenocarcinoma. In this investigation, the p53 status of a Welsh population of Barrett's-associated oesophageal adenocarcinomas were fully characterised at the gene sequence, chromosomal, mRNA and protein levels. In total, 31 tumours were examined for p53 gene sequence mutations using RFLP with sequencing, allelic loss of the gene was characterised by FISH, mRNA expression by p53 pathway signalling arrays and protein levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 39 publications
2
15
1
Order By: Relevance
“…The significance of the discordance between IHC-positive tumours and p53 mutation is unclear, although it is commonly reported (Gao et al, 2000;Babjuk et al, 2002;Doak et al, 2003). This discordance may suggest several hypotheses.…”
Section: Discussionmentioning
confidence: 67%
“…The significance of the discordance between IHC-positive tumours and p53 mutation is unclear, although it is commonly reported (Gao et al, 2000;Babjuk et al, 2002;Doak et al, 2003). This discordance may suggest several hypotheses.…”
Section: Discussionmentioning
confidence: 67%
“…However, 9 (26%) of these cases were strongly positive for p53 by immunohistochemistry. A more recent study found that whereas 19 of 29 adenocarcinomas strongly expressed p53 by immunohistochemistry, only 2 of these tumors had p53 mutations (26). Thus, it is clear that not all p53 mutations result in p53 protein accumulation and not all p53 protein accumulation is due to a p53 mutation.…”
Section: Relationship Between P53 Mutations and Immunohistochemical Ementioning
confidence: 98%
“…Approximately 90% of the mutations in p53 are point mutations (20). Many p53 mutations are thought to arise by oxidative damage to cytosine bases in exons 5 to 8 (26). Acid suppressive therapies may decrease oxidative DNA damage, although preceding p53 mutations seem to prevent this reduction (27).…”
Section: Mechanisms Of P53 Loss Of Functionmentioning
confidence: 99%
“…Endoscopic brushing cytology specimens are normally used for FISH analysis of molecular changes in EAC, but FFPE tissue is also an attractive and proven option [30]. Moreover, use of FFPE tissue allows retrospective sample analysis [31].…”
Section: Discussionmentioning
confidence: 99%